2012
DOI: 10.1152/ajpheart.01140.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia induces right heart failure in caveolin-1−/− mice

Abstract: Caveolin-1 (Cav-1)-/- mice develop mild pulmonary hypertension as they age. In this study, we sought to determine the effect of chronic hypoxia, an established model of pulmonary hypertension, on young Cav-1-/- mice with no measurable signs of pulmonary hypertension. Exposure of Cav-1-/- mice to chronic hypoxia resulted in an initial rise in right ventricular (RV) systolic pressure (RVSP) similar to wild-type (WT) mice. By three weeks RVSP decreased in the Cav-1-/- mice, whereas it was maintained in WT mice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
1
29
2
Order By: Relevance
“…Other studies also suggest that pulmonary artery pressure is not the sole factor regulating cardiac hypertrophy, and that cardiac hypoxia itself may be a stimulus for RV remodeling (45,46) through the up-regulation of gene expression (47,48). Animal models of RV pressure overload induced by pulmonary artery banding are not associated with RV failure (49), whereas pressure overload induced by hypoxia is (50,51). Bogaard and coworkers (46) compared the RV hypertrophic response to VEGF receptor inhibition (using SU5416) with that evoked by pulmonary artery banding in chronically hypoxic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also suggest that pulmonary artery pressure is not the sole factor regulating cardiac hypertrophy, and that cardiac hypoxia itself may be a stimulus for RV remodeling (45,46) through the up-regulation of gene expression (47,48). Animal models of RV pressure overload induced by pulmonary artery banding are not associated with RV failure (49), whereas pressure overload induced by hypoxia is (50,51). Bogaard and coworkers (46) compared the RV hypertrophic response to VEGF receptor inhibition (using SU5416) with that evoked by pulmonary artery banding in chronically hypoxic rats.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The development of PH in CAV-1 KO mice is accelerated by exposing animals to hypoxia. 28 We and others have reported a myeloid/BM origin of PH. Engraftment of serotonin 2B receptor-deficient BM in wild-type (WT) mice protected against the development of hypoxia-induced pulmonary vascular remodeling and elevation of RVSP in mice.…”
Section: Introductionmentioning
confidence: 83%
“…Trichrome staining was used to visualize and measure RV fibrosis 28,32,33 A Leica SCN400 F slide scanner (Leica Microsystems, Wetzlar, Germany) was used to scan images of whole slides at 320 magnification. Image Pro Plus 7.0. software was use for quantification of fibrosis area/total tissue area.…”
Section: Trichrome Staining and Quantificationmentioning
confidence: 99%
“…Our recent studies have identified nitration and the ensuing attenuation of PKG-1␣ activity in the lungs of lambs with pulmonary hypertension secondary to increased pulmonary blood flow and in lambs with rebound pulmonary hypertension associated with the acute withdrawal of inhaled NO therapy (1). In addition, the nitration and subsequent attenuation of PKG activity in the right ventricle appears to be responsible for the deterioration of right ventricle function in a mouse model of pulmonary hypertensive induced by chronic hypoxia (43). However, the increase in protein nitration associated with hypoxia reduces PKG activity through changes at the transcriptional and post-translational levels (2).…”
Section: Discussionmentioning
confidence: 99%